Preparation method and application of beta-FeOOH / fly ash-based composite aerogel
Patent Information
- Application Number
- CN202511235344.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-01
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-09-01
AI Technical Summary
处理粉煤灰的主要方法是土地沉积或填埋,这消耗了大量的土地资源
[0019] (1) The preparation method of β-FeOOH/fly ash based composite aerogel of the present invention is simple, green and environmentally friendly, and has low production cost. The process does not use toxic solvents such as DMF and DMAC in the traditional aerogel preparation, but uses water as the main solvent, which not only effectively reduces production cost, but also conforms to the concept of green and sustainable development, and provides environmental protection technology support for industrial scale-up.
Smart Images

Figure HDA0005574941070000011 
Figure HDA0005574941070000012 
Figure HDA0005574941070000013
Abstract
Description
Technical Field
[0001] This invention belongs to the field of composite material preparation technology, and in particular relates to a method for preparing β-FeOOH / fly ash-based composite aerogel and its application. Background Technology
[0002] With societal progress and deepening industrialization, water scarcity and pollution have significantly impacted the human living environment, making wastewater resource utilization crucial for addressing these issues. Activated carbon, alumina, silica, and iron oxide are commonly used adsorbents with high metal adsorption capacity, capable of adsorbing toxic and harmful substances in wastewater, such as heavy metal ions and organic matter. However, most of them are expensive and difficult to separate from wastewater after treatment.
[0003] As one of the major coal energy users in my country, coal combustion produces a significant amount of fly ash. The accumulation of fly ash consumes substantial land resources. Since the 1920s, the widespread use of coal has led to the generation of large quantities of fly ash and related byproducts. Globally, over 500 million tons of fly ash are generated annually due to coal-fired power generation, but only about 20% to 30% of this is reused in various regions. The main methods of fly ash disposal are landfilling or sedimentation, which consumes vast amounts of land resources. Furthermore, improper handling of fly ash, particularly its heavy metal content, poses a serious threat to natural ecosystems, leading to the degradation of plant and microbial life and further exacerbating environmental pollution. Moreover, with the annual increase in fly ash production, the corresponding management costs are also rising continuously. Therefore, implementing a cost-effective fly ash utilization strategy is crucial. Due to its porous structure and high specific surface area, fly ash possesses excellent adsorption properties, enabling it to adsorb toxic and harmful substances from wastewater. Therefore, applying fly ash to wastewater treatment as an adsorbent can achieve high-value resource utilization of solid waste, effectively solving the problems of land occupation and environmental pollution caused by its stockpiling. It can also replace some expensive traditional adsorbents (such as activated carbon), significantly reducing wastewater treatment costs. This "waste-to-waste" strategy not only opens up important avenues for the comprehensive utilization of fly ash but also provides an economical, efficient, and environmentally friendly dual solution to water scarcity and water pollution problems. Summary of the Invention
[0004] In view of this, to solve the above-mentioned technical problems, this invention proposes a method for preparing β-FeOOH / fly ash-based composite aerogel and its application in the field of wastewater treatment. The preparation method is simple, environmentally friendly, and low-cost. Fly ash is evenly distributed and presents a high proportion in the prepared β-FeOOH / fly ash-based composite aerogel, achieving high-quality utilization of the fly ash. The β-FeOOH / fly ash-based composite aerogel can efficiently adsorb toxic and harmful substances in wastewater, exhibits significant catalytic effects, and has the ability to purify wastewater.
[0005] To achieve the above objectives, the technical solution of the present invention is implemented as follows:
[0006] This invention provides a method for preparing β-FeOOH / fly ash-based composite aerogel, comprising the following steps:
[0007] S1. Dissolve cellulose, then add fly ash treated with acid solution and crosslinking agent in sequence. After reaction, let stand to obtain crude product.
[0008] S2. Add a pore-forming agent aqueous solution to the crude product, stir and allow it to foam naturally. After standing, soak it in water and dry it to obtain a hydrogel material with a three-dimensional network structure.
[0009] S3. The hydrogel material is immersed in an inorganic iron salt aqueous solution, heated, removed, washed, and dried to obtain the β-FeOOH / fly ash-based composite aerogel.
[0010] In some preferred embodiments of the preparation method of β-FeOOH / fly ash-based composite aerogel of the present invention, in step S1, the solvent system for dissolving cellulose is one or more combinations of sodium hydroxide and urea system, ionic liquid system, and ZnCl2 system.
[0011] In some preferred embodiments of the preparation method of β-FeOOH / fly ash-based composite aerogel of the present invention, in step S1, the acid solution is a hydrochloric acid solution or a sulfuric acid solution with a concentration of 0.5-3 mol / L, the ratio of acid solution to fly ash is 10-50 g fly ash per 30 mL acid solution, and the treatment time is 2-12 h; the mass ratio of cellulose to fly ash is 1:1-17.
[0012] In some preferred embodiments of the preparation method of β-FeOOH / fly ash-based composite aerogel of the present invention, in step S1, the crosslinking agent is one or a combination of epichlorohydrin, 1,6-hexanediol diglycidyl ether, and 1,4-butanediol diglyceride; the concentration of the crosslinking agent is 1-5 mol / L, and the molar ratio of the crosslinking agent to cellulose is 1:0.64-2.56.
[0013] In some preferred embodiments of the preparation method of β-FeOOH / fly ash-based composite aerogel of the present invention, in step S1, the reaction temperature is maintained at -20℃ to 20℃, and the standing time is 8 to 16 hours.
[0014] In some preferred embodiments of the preparation method of β-FeOOH / fly ash-based composite aerogel of the present invention, in step S2, the pore-forming agent is hydrogen peroxide, polyethylene glycol, polyurethane, sucrose microparticles or sodium dodecyl sulfate; the concentration of the aqueous solution of the pore-forming agent is 0.1-20 mg / mL; the molar ratio of the pore-forming agent to cellulose is 1:10-20; and the stirring time is 30 min-120 min.
[0015] In some preferred embodiments of the preparation method of β-FeOOH / fly ash-based composite aerogel of the present invention, in step S3, the inorganic iron salt is one or more of FeCl3, Fe2(SO4)3, Fe(NO3)3, and (FeSO4); the concentration of the inorganic iron salt aqueous solution is 0.8-40 mg / mL; the heating temperature is 60-180℃; and the heating time is 2-24 h.
[0016] A second aspect of the present invention provides a β-FeOOH / fly ash-based composite aerogel prepared by the preparation method described above.
[0017] The third aspect of this invention provides the application of the β-FeOOH / fly ash-based composite aerogel prepared by the aforementioned method in the field of wastewater purification and treatment.
[0018] Compared with existing technologies, the preparation method and application of the β-FeOOH / fly ash-based composite aerogel described in this invention have the following advantages:
[0019] (1) The preparation method of β-FeOOH / fly ash based composite aerogel of the present invention is simple, green and environmentally friendly, and has low production cost. The process does not use toxic solvents such as DMF and DMAC in the traditional aerogel preparation, but uses water as the main solvent, which not only effectively reduces production cost, but also conforms to the concept of green and sustainable development, and provides environmental protection technology support for industrial scale-up.
[0020] (2) The preparation method of the β-FeOOH / fly ash based composite aerogel of the present invention uses cellulose as a supporting framework. It has good biocompatibility, is renewable, has a large specific surface area, and its surface is rich in hydroxyl groups that can form hydrogen bond forces with fly ash, which effectively improves the problem of fly ash agglomeration, so that fly ash can be evenly distributed on its surface, ensuring the structural stability of the composite aerogel and the high exposure of active sites.
[0021] (3) The preparation method of β-FeOOH / fly ash based composite aerogel of the present invention uses industrial waste pollutant fly ash as an additive to convert industrial solid waste fly ash into a functional reinforcing phase, and the fly ash mass ratio in the product is as high as 93%, realizing the high-quality utilization of fly ash.
[0022] (4) The preparation method of β-FeOOH / fly ash based composite aerogel of the present invention uses in-situ growth method to uniformly anchor β-FeOOH nanoparticles on the surface of fly ash, constructing modified fly ash with catalytic degradation characteristics, which has good purification and treatment capabilities for wastewater, and realizes the treatment of waste with waste. Attached Figure Description
[0023] Figure 1 SEM image of the β-FeOOH / fly ash-based composite aerogel prepared in Example 1;
[0024] Figure 2 SEM image of the fly ash-based composite aerogel prepared in Example 1 without β-FeOOH loading;
[0025] Figure 3 The XRD pattern of the β-FeOOH / fly ash-based composite aerogel prepared in Example 1;
[0026] Figure 4 A physical image showing the lightweight properties of the β-FeOOH / fly ash-based composite aerogel prepared in Example 1.
[0027] Figure 5 A comparison of the catalytic performance of the β-FeOOH / fly ash-based composite aerogel prepared in Example 1 and the aerogel material prepared in Comparative Example 1 on wastewater.
[0028] Figure 6 A comparison of the catalytic performance of the β-FeOOH / fly ash-based composite aerogel prepared in Example 1 and the aerogel material prepared in Comparative Example 2 on wastewater.
[0029] Figure 7 XRD crystallinity calculation diagram of fly ash before and after pickling;
[0030] Figure 8 The graphs show the fly ash before and after pickling.
[0031] Figure 9 The diagram shows the catalytic cycle experiment of the β-FeOOH / fly ash-based composite aerogel prepared in Example 1. Detailed Implementation
[0032] Unless otherwise defined, the technical terms used in the following embodiments have the same meanings as commonly understood by those skilled in the art. Unless otherwise specified, the experimental reagents used in the following embodiments are conventional biochemical reagents; and the experimental methods described are conventional methods.
[0033] The present invention will now be described in detail with reference to the embodiments and accompanying drawings.
[0034] Example 1
[0035] S1. Add 6g of cellulose to the solution system of sodium hydroxide and urea, maintain the temperature at -20℃, and stir for 1 hour; after dissolving, add fly ash treated with sulfuric acid solution, with the amount added being 13:1 by mass of fly ash to cellulose (wherein, the concentration of sulfuric acid solution is 0.5mol / L, and the ratio of sulfuric acid solution to fly ash is 10-50g fly ash per 30mL of acid solution), and stir for 30 minutes; add 5ml of epichlorohydrin crosslinking agent with a concentration of 1mol / L, and stir for 30 minutes; after completion, let stand for 8 hours to obtain the crude product;
[0036] S2. Add 3 ml of 2 mol / L hydrogen peroxide aqueous solution to the crude product, stir for 30 min, let stand for 8 h, then soak in water until sodium hydroxide and urea are completely removed, freeze dry to obtain a hydrogel material with a three-dimensional network structure.
[0037] S3. Immerse the hydrogel material in a FeCl3·6H2O solution with a concentration of 18 mg / ml, maintain the mineralization temperature at 60℃, and mineralize for 16 h; after removal, wash and dry to obtain β-FeOOH / fly ash-based composite aerogel material.
[0038] Example 2
[0039] S1. Add 6g of cellulose to the solution system of sodium hydroxide and urea, maintain the temperature at -10℃, and stir for 2h. After dissolving, add fly ash treated with sulfuric acid solution, with the amount added being 11:1 by mass of fly ash to cellulose (wherein, the concentration of sulfuric acid solution is 1mol / L, and the ratio of sulfuric acid solution to fly ash is 10-50g fly ash per 30mL of acid solution), and stir for 10min. Add 6ml of epichlorohydrin crosslinking agent with a concentration of 2mol / L, and stir for 40min. After the process is complete, let stand for 12h to obtain the crude product.
[0040] S2. Add 5 ml of 3 mol / L hydrogen peroxide aqueous solution to the crude product, stir for 40 min, let stand for 12 h, then soak in water until sodium hydroxide and urea are completely removed, freeze dry to obtain a hydrogel material with a three-dimensional network structure.
[0041] S3. Immerse the hydrogel material in a FeCl3·6H2O solution with a concentration of 36 mg / ml, maintain the mineralization temperature at 70℃, and mineralize for 8 hours; after removal, wash and dry to obtain β-FeOOH / fly ash-based composite aerogel material.
[0042] Example 3
[0043] S1. Add 6g of cellulose to the solution system of sodium hydroxide and urea, maintain the temperature at -10℃, and stir for 3h. After dissolving, add fly ash treated with sulfuric acid solution, with the amount added being 9:1 by mass of fly ash to cellulose (wherein, the concentration of sulfuric acid solution is 2mol / L, and the ratio of sulfuric acid solution to fly ash is 10-50g fly ash per 30mL of acid solution), and stir for 20min. Add 8ml of epichlorohydrin crosslinking agent with a concentration of 3mol / L, and stir for 50min. After completion, let stand for 12h to obtain the crude product.
[0044] S2. Add 10 ml of 4 mol / L polyethylene glycol aqueous solution to the crude product, stir for 70 min, let stand for 14 h, then soak in water until sodium hydroxide and urea are completely removed, and freeze dry to obtain a hydrogel material with a three-dimensional network structure.
[0045] S3. Immerse the hydrogel material in a FeCl3·6H2O solution with a concentration of 18 mg / ml, maintain the mineralization temperature at 80℃, and mineralize for 24 h; after removal, wash and dry to obtain β-FeOOH / fly ash-based composite aerogel material.
[0046] Example 4
[0047] S1. Add 6g of cellulose to the solution system of sodium hydroxide and urea, maintain the temperature at 0℃, and stir for 4h. After dissolution, add fly ash treated with sulfuric acid solution, with the amount added being 7:1 by mass of fly ash to cellulose (wherein, the concentration of sulfuric acid solution is 2.5mol / L, and the ratio of sulfuric acid solution to fly ash is 10-50g fly ash per 30mL of acid solution), and stir for 40min. Add 7ml of epichlorohydrin crosslinking agent with a concentration of 4mol / L, and stir for 80min. After completion, let stand for 15h to obtain the crude product.
[0048] S2. Add 10 ml of 6 mol / L polyethylene glycol aqueous solution to the crude product, stir for 80 min, let stand for 15 h, then soak in water until sodium hydroxide and urea are completely removed, and freeze dry to obtain a hydrogel material with a three-dimensional network structure.
[0049] S3. Immerse the hydrogel material in a FeCl3·6H2O solution with a concentration of 18 mg / ml, maintain the mineralization temperature at 60℃, and mineralize for 16 h; after removal, wash and dry to obtain β-FeOOH / fly ash-based composite aerogel material.
[0050] Example 5
[0051] S1. Add 6g of cellulose to the solution system of sodium hydroxide and urea, maintain the temperature at -20℃, and stir for 1 hour. After dissolving, add fly ash treated with sulfuric acid solution, with the amount added being 13:1 by mass of fly ash to cellulose (wherein, the concentration of sulfuric acid solution is 0.5mol / L, and the ratio of sulfuric acid solution to fly ash is 10-50g fly ash per 30mL of acid solution), and stir for 30 minutes. Add 9ml of epichlorohydrin crosslinking agent with a concentration of 5mol / L, and stir for 30 minutes. After completion, let stand for 8 hours to obtain the crude product.
[0052] S2. Add 7 ml of 5 mol / L hydrogen peroxide aqueous solution to the crude product, stir for 90 min, let stand for 10 h, then soak in water until sodium hydroxide and urea are completely removed, freeze dry to obtain a hydrogel material with a three-dimensional network structure.
[0053] S3. Immerse the hydrogel material in a FeCl3·6H2O solution with a concentration of 18 mg / ml, maintain the mineralization temperature at 60℃, and mineralize for 16 h; after removal, wash and dry to obtain β-FeOOH / fly ash-based composite aerogel material.
[0054] Example 6
[0055] S1. Add 6g of cellulose to the solution system of sodium hydroxide and urea, maintain the temperature at -20℃, and stir for 1h. After dissolving, add fly ash treated with sulfuric acid solution, with the amount added being 13:1 by mass of fly ash to cellulose (wherein, the concentration of sulfuric acid solution is 0.5mol / L, and the ratio of sulfuric acid solution to fly ash is 10-50g fly ash per 30mL of acid solution), and stir for 30min. Add 7ml of epichlorohydrin crosslinking agent with a concentration of 3mol / L, and stir for 30min. After the process is complete, let stand for 8h to obtain the crude product.
[0056] S2. 11 ml of 7 mol / L hydrogen peroxide aqueous solution was added to the crude product, stirred for 70 min, allowed to stand for 9 h, and then soaked in water until sodium hydroxide and urea were completely removed. After freeze-drying, a hydrogel material with a three-dimensional network structure was obtained.
[0057] S3. Immerse the hydrogel material in a FeCl3·6H2O solution with a concentration of 18 mg / ml, maintain the mineralization temperature at 60℃, and mineralize for 16 h; after removal, wash and dry to obtain β-FeOOH / fly ash-based composite aerogel material.
[0058] Example 7
[0059] S1. Add 6g of cellulose to the solution system of sodium hydroxide and urea, maintain the temperature at -20℃, and stir for 1h. After dissolving, add fly ash treated with sulfuric acid solution, with the amount added being 13:1 by mass of fly ash to cellulose (wherein, the concentration of sulfuric acid solution is 0.5mol / L, and the ratio of sulfuric acid solution to fly ash is 10-50g fly ash per 30mL of acid solution), and stir for 30min. Add epichlorohydrin crosslinking agent, with a concentration of 1mol / L, 12ml, and stir for 30min. After completion, let stand for 8h to obtain the crude product.
[0060] S2. Add 13 ml of 8 mol / L hydrogen peroxide aqueous solution to the crude product, stir for 60 min, let stand for 11 h, then soak in water until sodium hydroxide and urea are completely removed, and freeze dry to obtain a hydrogel material with a three-dimensional network structure.
[0061] S3. Immerse the hydrogel material in a FeCl3·6H2O solution with a concentration of 18 mg / ml, maintain the mineralization temperature at 60℃, and mineralize for 16 h; after removal, wash and dry to obtain β-FeOOH / fly ash-based composite aerogel material.
[0062] Example 8
[0063] S1. Add 6g of cellulose to the solution system of sodium hydroxide and urea, maintain the temperature at -20℃, and stir for 1h; after dissolving, add fly ash treated with sulfuric acid solution, the amount added is based on the mass ratio of fly ash to cellulose of 13:1 (wherein, the concentration of sulfuric acid solution is 0.5mol / L, and the ratio of sulfuric acid solution to fly ash is 10-50g fly ash per 30mL of acid solution), and stir for 30min; add epichlorohydrin crosslinking agent, the concentration of crosslinking agent is 4mol / L, add 20ml, and stir for 30min; after finishing, let stand for 8h to obtain crude product;
[0064] S2. Add 25 ml of 10 mol / L hydrogen peroxide aqueous solution to the crude product, stir for 40 min, let stand for 14 h, then soak in water until sodium hydroxide and urea are completely removed, freeze dry to obtain a hydrogel material with a three-dimensional network structure.
[0065] S3. Immerse the hydrogel material in a FeCl3·6H2O solution with a concentration of 18 mg / ml, maintain the mineralization temperature at 100℃, and mineralize for 16 h; after removal, wash and dry to obtain β-FeOOH / fly ash-based composite aerogel material.
[0066] Comparative Example 1
[0067] S1. Add 6g of cellulose to the solution system of sodium hydroxide and urea, maintain the temperature at -20℃, and stir for 1h; add 5ml of epichlorohydrin crosslinking agent with a concentration of 1mol / L, and stir for 30min; after the end, let stand for 8h to obtain the crude product.
[0068] S2. Add 3 ml of 20 mg / ml hydrogen peroxide aqueous solution to the crude product, stir for 50 min, let stand for 8 h, then soak in water until sodium hydroxide and urea are completely removed, freeze dry to obtain a hydrogel material with a three-dimensional network structure.
[0069] S3. Immerse the hydrogel material in a FeCl3·6H2O solution with a concentration of 18 mg / ml, maintain the mineralization temperature at 100℃, and mineralize for 16 h; after removal, wash and dry to obtain β-FeOOH / fly ash-based composite aerogel material.
[0070] Comparative Example 2
[0071] S1. Add 6g of cellulose to the solution system of sodium hydroxide and urea, maintain the temperature at -20℃, and stir for 1h. After dissolving, add fly ash treated with sulfuric acid solution, with the amount added being 13:1 by mass of fly ash to cellulose (wherein, the concentration of sulfuric acid solution is 0.5mol / L, and the ratio of sulfuric acid solution to fly ash is 10-50g fly ash per 30mL of acid solution), and stir for 30min. Add 7ml of epichlorohydrin crosslinking agent with a concentration of 1mol / L, and stir for 30min. After the process is complete, let stand for 8h to obtain the crude product.
[0072] S2. Soak the crude product in water until sodium hydroxide and urea are completely removed, and freeze-dry to obtain a hydrogel material with a three-dimensional network structure.
[0073] S3. Immerse the hydrogel material in a FeCl3·6H2O solution with a concentration of 18 mg / ml, maintain the mineralization temperature at 100℃, and mineralize for 16 h; after removal, wash and dry to obtain β-FeOOH / fly ash-based composite aerogel material.
[0074] Performance testing:
[0075] 1. SEM analysis was performed on the β-FeOOH / fly ash-based composite aerogel prepared in Example 1 (using Example 1 as an example; the SEM images of the other examples are similar). The results are presented by... Figure 1 It can be seen that β-FeOOH nanoparticles are uniformly distributed on the surface of fly ash, and the β-FeOOH nanoparticles exhibit a clear nanorod morphology.
[0076] 2. SEM analysis was performed on the β-FeOOH / fly ash-based composite aerogel prepared in Example 1 (Example 1 was used as an example; the SEM images of the other examples were similar). The results were obtained from... Figure 2 It is known that fly ash is evenly distributed on the surface of cellulose. This is because there is an interaction force between fly ash and cellulose, and hydrogen bonds exist. Therefore, using cellulose as a supporting skeleton can effectively solve the problem of fly ash accumulation.
[0077] 3. XRD analysis was performed on the β-FeOOH / fly ash-based composite aerogel prepared in Example 1 (Example 1 is used as an example; the XRD patterns of other examples are similar). Results are presented by... Figure 4 It can be seen that new characteristic peaks appeared in the spectrum at 2θ = 11.8°, 26.7°, 35.2°, 39.2°, and 56.0°, respectively. The positions of these peaks highly match the standard diffraction peaks of β-FeOOH (PDF#34-1266), corresponding to the (110), (310), (211), (301), and (521) crystal planes, respectively. This result confirms the successful loading of β-FeOOH and its uniform distribution on the material surface.
[0078] 4. The weight of the β-FeOOH / fly ash-based composite aerogel prepared in Example 1 was analyzed (using Example 1 as an example). The results are presented by... Figure 4 It can be seen that the prepared β-FeOOH / fly ash-based composite aerogel material stands stably on dandelion without any signs of bending, indicating the lightweight characteristics of the prepared β-FeOOH / fly ash-based composite aerogel material. Even when the mass ratio of fly ash loading reaches 93%, the product can still stand stably on dandelion, which also indicates that the addition of pore-forming agent increases its porosity and reduces its density, further optimizing its lightweight characteristics.
[0079] 5. The catalytic performance of the β-FeOOH / fly ash-based composite aerogel materials prepared in Examples 1-8 of this invention and the aerogel materials prepared in Comparative Examples 1 and 2 was tested using a 50 mg / L methylene blue solution. The test method was conducted under 300 W sunlight and 1 ml of 20 mmol / L hydrogen peroxide solution. The experimental results are shown in Table 1:
[0080] Table 1
[0081] Example 1 99.5 Example 2 98.7 Example 3 97.6 Example 4 96.5 Example 5 98.4 Example 6 98.8 Example 7 97.5 Example 8 96.8 Comparative Example 1 83.5 Comparative Example 2 80.5
[0082] 6. The catalytic performance of the β-FeOOH / fly ash-based composite aerogel prepared in Example 1 and the aerogel material prepared in Comparative Example 1 were compared and analyzed. The results are presented in... Figure 5 It can be seen that the β-FeOOH / fly ash-based composite aerogel prepared in Example 1 has a significant catalytic effect on methylene blue, with a residual rate of only 0.5% after 3 minutes. In contrast, the aerogel material prepared in Comparative Example 1 without the addition of fly ash still has a residual rate of more than 50% within 3 minutes. This further proves that the addition of fly ash can increase its catalytic degradation efficiency.
[0083] 7. The catalytic performance of the β-FeOOH / fly ash-based composite aerogel prepared in Example 1 and the aerogel material prepared in Comparative Example 2 were compared and analyzed. The results are presented in... Figure 6 It can be seen that the catalytic effect of the β-FeOOH / fly ash-based composite aerogel prepared in Example 1 with the addition of a porogen is better than that of Comparative Example 2 without the addition of a porogen. This is because the addition of a porogen can increase the porosity and surface area, providing more reaction sites.
[0084] 8. Detection of crystallinity of fly ash before and after acid washing (the fly ash was treated with sulfuric acid solution at a concentration of 0.5 mol / L, and the ratio of sulfuric acid solution to fly ash was 10-50 g fly ash per 30 mL acid solution): Results are presented by... Figure 7 It can be seen from the XRD crystallinity calculations of fly ash FA before and after acid washing that the crystallinity decreases after acid washing. This is because the acid washing environment damages the surface structure, exposing more reactive sites. Figure 8 It can be seen that the specific surface area of fly ash CFA increases after acid washing, which further proves that it generates more reactive sites, which is beneficial to reduce fly ash accumulation and agglomeration.
[0085] 9. Repeated catalytic cycle testing was performed on the β-FeOOH / fly ash-based composite aerogel material prepared in Example 1: (The text abruptly ends here, likely due to an incomplete sentence or missing information.) Figure 9 It can be seen that after five cycles, its catalytic effect can still reach more than 85%.
[0086] In summary, the β-FeOOH / fly ash-based composite aerogel material prepared by this invention has low raw material cost, simple preparation process, and significant catalytic effect, making it suitable for large-scale production. Furthermore, acid washing of fly ash generates more reactive sites, reducing fly ash accumulation and agglomeration problems. The β-FeOOH / fly ash-based composite aerogel material prepared using the examples exhibits high catalytic effect on dyes and antibiotic solutions, is reusable, and is cost-effective.
[0087] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing β-FeOOH / fly ash-based composite aerogel, characterized in that, Includes the following steps: S1. Dissolve cellulose, then add acid-treated fly ash and crosslinking agent sequentially. After reaction, let stand to obtain crude product; wherein, the mass ratio of cellulose to fly ash is 1:1 to 17; the acid solution is hydrochloric acid solution or sulfuric acid solution with a concentration of 0.5 to 3 mol / L; the molar ratio of crosslinking agent to cellulose is 1:0.64 to 2.
56. S2. Add an aqueous solution of porogen to the crude product, stir and allow it to foam naturally. After standing, soak it in water and dry to obtain a hydrogel material with a three-dimensional network structure. The molar ratio of porogen to cellulose is 1:10-20. S3. The hydrogel material is immersed in an inorganic iron salt aqueous solution, heated, removed, washed, and dried to obtain the β-FeOOH / fly ash-based composite aerogel.
2. The preparation method of β-FeOOH / fly ash-based composite aerogel according to claim 1, characterized in that: In S1, the solvent system for dissolving cellulose is one or a combination of sodium hydroxide and urea system, ionic liquid system, and ZnCl2 system.
3. The preparation method of β-FeOOH / fly ash-based composite aerogel according to claim 1, characterized in that: In step S1, the ratio of acid solution to fly ash is 10-50g fly ash per 30mL of acid solution, and the treatment time is 2-12h.
4. The preparation method of β-FeOOH / fly ash-based composite aerogel according to claim 1, characterized in that: In S1, the crosslinking agent is one or a combination of epichlorohydrin, 1,6-hexanediol diglycidyl ether, and 1,4-butanediol diglyceride ethyl ether; the concentration of the crosslinking agent is 1 to 5 mol / L.
5. The preparation method of β-FeOOH / fly ash-based composite aerogel according to claim 1, characterized in that: In step S1, the reaction temperature is maintained at -20℃ to 20℃, and the settling time is 8 to 16 hours.
6. The preparation method of β-FeOOH / fly ash-based composite aerogel according to claim 1, characterized in that: In step S2, the pore-forming agent is hydrogen peroxide, polyethylene glycol, sucrose microparticles, or sodium dodecyl sulfate; the stirring time is 30 min to 120 min.
7. The preparation method of β-FeOOH / fly ash-based composite aerogel according to claim 1, characterized in that: In S3, the inorganic iron salt is one or more of FeCl3, Fe2(SO4)3, Fe(NO3)3, and FeSO4; the concentration of the inorganic iron salt aqueous solution is 0.8–40 mg / mL; the heating temperature is 60–180 °C; and the heating time is 2–24 h.
8. β-FeOOH / fly ash-based composite aerogel prepared by the preparation method according to any one of claims 1 to 7.
9. The use of the β-FeOOH / fly ash-based composite aerogel prepared by the preparation method according to any one of claims 1 to 7, characterized in that: Applications in the field of wastewater purification and treatment.
Citation Information
Patent Citations
Preparation method of cellulose-based composite aerogel
CN117398978A
Method for preparing composite aerogel by using fly ash and waste mixed cellulose membrane as raw materials
CN117797735A